The Role of Kenya Meteorological Service in Weather Early Warning in Kenya. (12th March 2015) - Shilenje, Zablon W.; Ogwang, Bob A.
Abstract : Early warning in weather forecasting entails provision of timely and effective weather information that allows individuals, organisations, or communities exposed to likely weather hazards to take action that avoids or reduces their exposure to risks. Various sectors have developed different ways to mitigate the effects of climate anomalies. The study reviews the existing monitoring and response structures, and communications flow channels of weather data at different levels, focusing on the role of Kenya Meteorological Service (KMS). The methodology employed was literature review of various documents. The study argues that early warning and weather information communication are essential elements for effective governance of weather risks through a well-developed warning system. At the end, the study recommends strengthening the existing structures with respect to weather monitoring, processing, and dissemination of weather products to end users.